Sistem Monitoring Suhu dan Counter Running Mesin Auto Cutter Gerber Berbasis Internet of Things - Nashruddin, Yunus; Wijiyanto, W; Susanto, Rudi (LPPM STIKOM Tunas Bangsa, 2024)
This study aims to create a reading system for the running of the Gerber Auto Cutter machine and monitor the temperature in the vacuum mechanism area of the machine, which can provide notifications to the telegram chatbot and Arduino IoT cloud. In this case, the reading of the running machine functions to detect machine usage in real time and accurately, both when the machine is turned on and when the machine is running for the fabric cutting process in production. From the reading of the running machine, data can be taken on how long the machine and knife have been used, so that they can be programmed to display notifications on the telegram chatbot when a certain usage time has been reached. For reading the temperature in the vacuum mechanism room, it functions to monitor and provide notifications when it has exceeded the temperature threshold that can be tolerated by the electrical system in the vacuum system. In this case, the condition of the machine stopping operating due to damage to parts can be minimized. This study uses a qualitative method by means of observation, interviews, literature studies and case studies at PT. Brothersindo Saudara Sejati which is a machine supplier. The author uses the waterfall method for software development and prototyping for hardware development.